Tertiary education leadership programmes in Tanzania and New Zealand : higher education for social development : a thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy in Education, Massey University College of Education, Palmerston North, New Zealand - Alphonce, Ndibalema Rwekaka (Massey University, 2000)
This thesis, about educational leadership development, explores selected tertiary programmes of educational leadership in New Zealand and Tanzania. The aim of the study was to explore whether, and how, Tanzanian programme development could benefit from the experience of programme development which has been acquired by New Zealand's tertiary institutions. For the purpose of the study, five programmes offered by tertiary institutions in New Zealand and courses from the, then, only tertiary educational leadership programme in Tanzania, were selected for examination. The study examined the context of educational leadership in both Tanzania and New Zealand, with particular reference to the contemporary reforms in education in the two countries and their influence on educational leadership development in recent years. The specific contents of the programmes were also examined in respect to their organisational, cognitive and affective aspects. Employing an eclectic qualitative research methodology, the study was underpinned by critical theory assumptions in advocating a framework for educational leadership programme development in the context of Tanzania, based on the concept of power diffusion, allowing for a more broad based democratic participation of teachers in leadership programmes. Premised on the assumption that educational leadership is central to the success or failure of any educative process in its conception of leadership, the thesis advocates the development of democratic, dialogic, participative and reflective leadership as opposed to leadership based on autocratic and power-wielding authority. The main thrust of the arguments rest on the understanding that, without the teachers' enthusiasm to teach and the learners' willingness to learn, schools would be nothing but "a wilderness of wasted logic". It is argued that educational leadership can contribute significantly towards the realisation of the ideal, albeit not necessarily clinical, environment for the educative process to take place. It is contended that, in the context of the contemporary social and political structures, especially in developing countries, such as Tanzania, educational leadership can either be for liberation or domination. Based on the findings from various New Zealand and Tanzanian programmes of educational leadership, examined in this study, it is underscored that, in order to be liberative, educational leadership requires the support of a socially critical philosophy. The findings of the thesis highlight the centrality of the role of tertiary education institutions in the development of leadership in educational places. Thus, it is concluded that, for a developing nation, like Tanzania, the need for tertiary programmes for educational leadership cannot be overemphasised.
Keywords: Educational leadership; Teachers; In-service training; School administrators; School principals; New Zealand; Tanzania; Fields of Research::330000 Education::330300 Professional Development of Teachers